2023
DOI: 10.1186/s12879-023-08328-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of previous infection with SARS-CoV-2 in protecting against omicron reinfections and severe complications of COVID-19 compared to pre-omicron variants: a systematic review

Maryam Arabi,
Yousef Al-Najjar,
Omna Sharma
et al.

Abstract: Background The SARS-CoV-2 virus elicited a major public concern worldwide since December 2019 due to the high number of infections and deaths caused by COVID-19. The Omicron variant was detected in October 2021 which evolved from the wild-type SARS-CoV-2 and was found to possess many mutations. Omicron exhibited high transmissibility and immune evasion as well as reduced severity when compared to the earlier variants. Although vaccinated individuals were largely protected against infections in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 94 publications
3
11
0
Order By: Relevance
“…Another comprehensive approach by Arabi et al certified that earlier infection protects against Omicron, even though the degree of immunity was much lower relative to Delta. These authors concluded that optimal protection is not provided by vaccination or previous infection, but rather through hybrid immunity [ 54 ]. Lastly, Notarte et al systematically reviewed the impact of COVID-19 vaccination on the risk of developing long COVID and related symptoms, revealing that the majority of analyzed papers reached a consensus regarding the improvement of long COVID symptoms following at least one dose post vaccination [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another comprehensive approach by Arabi et al certified that earlier infection protects against Omicron, even though the degree of immunity was much lower relative to Delta. These authors concluded that optimal protection is not provided by vaccination or previous infection, but rather through hybrid immunity [ 54 ]. Lastly, Notarte et al systematically reviewed the impact of COVID-19 vaccination on the risk of developing long COVID and related symptoms, revealing that the majority of analyzed papers reached a consensus regarding the improvement of long COVID symptoms following at least one dose post vaccination [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…A significant portion of convalescent COVID-19 patients, estimated at 10–30% (over 30 million people in the U.S., 20 million in Europe, and up to 180 million worldwide) may experience long COVID [ 17 ]. The wide variation in the estimated prevalence of long COVID within and between countries may result from a number of determinants, including the age and sex of subjects, comorbid health conditions, the timing of assessment, sociodemographic factors, self-reported questionnaire variabilities, etc.…”
Section: Introductionmentioning
confidence: 99%
“…With the initial emergence of the SARS-CoV-2 Omicron variant of concern (VoC) in 2021, greater vaccine breakthrough and reinfection of previously infected individuals was observed 3 . This was in large part due to numerous mutations in the viral S protein, particularly in the receptor binding domain (RBD) which allowed for immune evasion.…”
Section: Introductionmentioning
confidence: 99%